Displacement-constrained vibration-attenuation controller design for linear structure systems with parameter uncertainties. (2016) - Ding, Yuanchun; Weng, Falu; Ge, Ji; Nguyen, John
Two aspects, occupants' comfort and structural safety, need to be considered in the presence of the control problems of linear structure systems. In this paper, the two aspects are described by two controlled objectives. They are movements of the floors to the ground and the maximum relative displacements between adjacent floors. To achieve the two objectives, the method with a combination of H∞ and energy-to-peak control is adopted to guarantee the asymptotic stability of the structural system with external perturbation. Using matrix transformation, the structural system is described by a state-space model. Then, the LMI-based conditions are deduced from the model to asymptotically stabilise the system. By solving these LMIs, the controllers can be established for the structural system with a prescribed level of disturbance attenuation. Finally, an example is given to illuminate the effectiveness of the proposed method.